LEPROSY NEUROPATHY - Fahrani Yossa Prachika; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Leprosy is a major cause of peripheral neuropathy in developing countries, affecting sensory, motor, and autonomic nerve function. Neuropathy complications can include sensory loss and muscle weakness. Impaired sensory nerve function is often the first symptom encountered in leprosy neuropathy. Early detection and treatment of neuropathy in leprosy are important to prevent disability.